Modelling powder core inductors for passive filters in inverters using finite element analysis. Issue 3 (1st February 2017) - Jayalath, S.; Ongayo, D.; Hanif, M.
Abstract : Properties of powder core based inductors when utilised in a passive filter of the voltage source inverter are investigated to highlight the importance of considering the soft‐saturation nature of powder materials in determining the inductance when subjected to varying load current. Simulations were carried out in ANSYS Maxwell and Simplorer to understand the magnetic behaviour of inductors under pulse width modulation in a three‐phase inverter. Variation of the effective inductance due to soft saturation nature of the powder cores is utilised to achieve the inductance demanded by the passive filter at the design stage.